Hyponatraemic seizures following prostate brachytherapy. Issue 3 (11th June 2014) - Slevin, Finbar; Rodda, Sree Lakshmi; Bosomworth, Mike; Bottomley, David
Abstract Aim To demonstrate the importance of fluid management in the perioperative period by presenting a case of hyponatraemic seizures following prostate brachytherapy. Case A 61-year-old gentleman, who had prostate cancer but was otherwise well, developed confusion and word-finding difficulties the day after prostate brachytherapy. This was followed by tonic–clonic seizures that necessitated treatment, intubation and ventilation, and admission to the intensive care unit. Investigations revealed serum sodium of 116 mmol/L. Fluid balance was inadequately recorded, but the patient had drank more than 3 L of water before he developed hyponatraemia. Discussion Postoperative severe hyponatraemia and hyponatraemic encephalopathy develop because of anti-diuretic hormone release and hypotonic fluid administration. These are medical emergencies and should be managed in an intensive care unit. Symptoms range from headache, nausea and confusion to seizures, respiratory arrest and death, and are related to cerebral oedema. Treatment is done using hypertonic sodium chloride to increase the serum sodium to safe levels. Care should be taken to avoid overly rapid correction of serum sodium. Complete documentation of fluid balance is essential to allow proper assessment of fluid status. Patients should be advised on appropriate oral fluids in the postoperative period.